2015
DOI: 10.1093/icesjms/fsv130
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of ocean acidification on the microbial food web under different trophic conditions

Abstract: We investigated the effects of an increase in dissolved CO2 on the microbial communities of the Mediterranean Sea during two mesocosm experiments in two contrasting seasons: winter, at the peak of the annual phytoplankton bloom, and summer, under low nutrient conditions. The experiments included treatments with acidification and nutrient addition, and combinations of the two. We followed the effects of ocean acidification (OA) on the abundance of the main groups of microorganisms (diatoms, dinoflagellates, nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
80
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 53 publications
14
80
1
Order By: Relevance
“…plankton communities can occur under prolonged low-nutrient conditions, where observed variability in biomass is generally low. This conclusion is in line with recent studies in different oceanic regions, which reported most prominent effects of OA when inorganic nutrients were depleted (Paul et al, 2015;Sala et al, 2015;Bach et al, 2016). However, our study is the first to demonstrate this for oligotrophic waters of the subtropical North Atlantic.…”
Section: Plankton Community Structure and Influence Of Ocean Acidificsupporting
confidence: 94%
See 1 more Smart Citation
“…plankton communities can occur under prolonged low-nutrient conditions, where observed variability in biomass is generally low. This conclusion is in line with recent studies in different oceanic regions, which reported most prominent effects of OA when inorganic nutrients were depleted (Paul et al, 2015;Sala et al, 2015;Bach et al, 2016). However, our study is the first to demonstrate this for oligotrophic waters of the subtropical North Atlantic.…”
Section: Plankton Community Structure and Influence Of Ocean Acidificsupporting
confidence: 94%
“…The few reported community-level studies mostly focused on rather eutrophic environments at higher latitudes, such as the Arctic Ocean or temperate waters, since these regions are commonly assumed to be most vulnerable to ongoing changes in carbonate chemistry (Orr et al, 2005;Yamamoto-Kawai et al, 2009). However, recent evidence from the Baltic Sea, North Sea, and Mediterranean Sea indicated that OA effects might be most pronounced when inorganic nutrient concentrations are low (Paul et al, 2015;Sala et al, 2015;Bach et al, 2016;Hornick et al, 2016). How plankton communities in the vast oligotrophic regions of the subtropical gyres might respond to OA is presently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, major nutrients sometimes become depleted late in the season on McMurdo Sound, the origin of our culture isolates, as Fe inputs are somewhat higher in these nearshore waters (Bertrand et al, 2015). Experiments using nutrient-limited phytoplankton frequently find differing responses to CO 2 and temperature compared to those of nutrient-replete cells, including sometimes enhanced effects of these global change factors on elemental ratios (Taucher et al, 2015;Sala et al, 2016). Our experiments under high-nutrient, Fe-replete conditions thus are likely to best predict possible biological effects of future high CO 2 and temperature during the first half or more of the Ross Sea growing season.…”
Section: Discussionmentioning
confidence: 97%
“…Recent mesocosm experiments showed that OA effects can be particularly pronounced during extended periods of low inorganic nutrient concentrations (Paul et al, 2015;Sala et al, 2015;Bach et al, 2016;Thomson et al, 2016). We therefore conducted an in situ mesocosm experiment in the eastern subtropical Atlantic Ocean off the coast of Gran Canaria (Canary Islands)-a region characterized by low concentrations of inorganic nutrients in particular during fall when the study took place (Arístegui et al, 2001).…”
Section: Introductionmentioning
confidence: 99%